Українському народу – стабільний планомірностійкий розвиток (історико-аналітичні нариси: переосмислення минулого). Частина 3. Ретроспектива становлення планово-економічної самостійності на різних рівнях управління: ідеї, люди, судьби - Фокін, В.П. (Вісник економічної науки України, 2022)
У статті розкриті результати переосмислення становлення планово-економічної самостійності підприємств, об'єднань і галузей промисловості народного господарства (з конкретизацією на прикладі вугільної промисловості України) під впливом Міжвідомчої комісії з впровадження нових систем планування і організації управління Держплану УРСР в 1976-1990 роках. В контексті усвідомлення положень доктрини "3-х С" (Соціальне прогнозування, Соціальне планування, Соціальне управління) здійснено стратегування стабільного людиноцентриського розвитку. Обґрунтована необхідність доопрацювання проєкту 2011, 2017 і 2020 років Закону України "Про державне планування" як основи побудови Планового кодексу України. Наведений досвід формування Сектором проблем ефективності управління ЕНДІ Держплану УРСР науково-методичного забезпечення розробки на 1976-1980, 1981-1985, 1986-1990 роки Плану вдосконалення управління галузями народного господарства підвідомчого Уряду УРСР кола міністерств і відомств республіки. На основі обґрунтування планового механізму гармонізації суспільних, колективних і особистих економічних інтересів розкрито сутність ініціативних наукових наробок Сектору проблем ефективності управління ЕНДІ Держплану УРСР стосовно моделювання програмно-цільового індикативного планування соціально-орієнтованої економіки республіки у складі Союзу РСР. Наведений приклад комплексного проєктування цілісної ефективної і гнучкої системи управління шахт, вугільних комбінатів, галузі в цілому в умовах планово-економічної самостійності УРСР у складі СРСР. Розглянуті, як альтернатива діючої англосаксонської моделі відкритого ринку з вільними цінами, методологічні положення двосекторної моделі змішаної економіки "План-Ринок", яку доцільно використовувати для уточнення і вдосконалення діючої в Україні ринкової моделі економіки. В статті приділено увагу реальному прикладу підбору і підготовці вітчизняних управлінських кадрів з новаторськими ідеями державотворення на прикладі наукових напрацювань д.е.н., професора Столярова Василя Федосійовича в 1972-1994 роках від аспіранта стаціонару до директора ЕНДІ Держплану УРСР. Сформульовані питання для публічного обговорення в Дискусійному клубі Академії економічних наук України. The article reveals the results of rethinking the formation of planning and economic independence of enterprises, associations and industries of the national economy (with specification on the example of the coal industry of Ukraine) under the influence of the Interdepartmental Commission for the Implementation of New Systems of Planning and Management Organization of the State Plan of the Ukrainian SSR in 1976-1990. In the context of awareness of the provisions of the "three S" doctrine (Social forecasting, Social planning, Social management), the strategizing of stable human-centered development has been carried out. The need to finalize the 2011, 2017 and 2020 draft of the Law of Ukraine "On State Planning" as a basis for building the Planning Code of Ukraine is justified. The experience of formation of the Sector of problems of the efficiency of management of Economic Research Institute of the State Plan of the Ukrainian SSR for scientific and methodological support of the development for the years 1976-1980, 1981-1985, 1986-1990 of the Plan for improving the management of the branches of the national economy of the subdepartmental Government of the Ukrainian SSR circle of ministries and departments of the republic is given. Based on the substantiation of the planned mechanism of harmonization of public, collective and personal economic interests, the essence of the initiative scientific work of the Sector of the Management Effectiveness of Economic Research Institute of the State Plan of the Ukrainian SSR regarding the modeling of the programtarget indicative planning of the socially-oriented economy of the republic as part of USSR was revealed. An example of integrated design of a comprehensive effective and flexible management system of mines, coal plants, industry as a whole in the conditions of planning and economic independence of the Ukrainian SSR as part of the USSR is given. Considered, as an alternative to the current Anglo-Saxon model of an open market with free prices, the methodological provisions of the two-sector model of the mixed economy "Market-Plan", which should be used to clarify and improve the current market model of the economy in Ukraine. The article pays attention to a real example of the selection and training of domestic management personnel with innovative ideas of state-building, based on the example of the scientific work of Doctor of Economics, Professor Stolyarov Vasyl Fedosiyovych in 1972-1994, from a full-time graduate student of the university to the director of the Economic Research Institute of the State Plan of the Ukrainian SSR. Formulated questions for public discussion in the Discussion Club of the Academy of Economic Sciences of Ukraine.